Penguatan Pendekatan Pembelajaran dan Gaya Belajar Melalui Sikap Ilmiah IPA: Penelitian - Nur Rizkiyah; Yulistiana Yulistiana (Lembaga Penelitian dan Pengabdian Masyarakat, 2026)
The purpose of this study is to determine the effect of learning approaches on scientific attitudes in science, to determine the effect of learning styles on scientific attitudes in science. Furthermore, to determine the effect of learning approaches and learning styles together on scientific attitudes in science. The research method used is an experimental method with a 2x2 factorial design, the sample used was 120 students of class V111 of private MTs Tangerang. The results of this study are There is a significant effect of learning approaches on scientific attitudes in science of private MTs students in South Tangerang City. (1), There is a significant effect of learning styles on scientific attitudes in science of private MTs students in South Tangerang City. (2), There is no significant interaction effect of learning styles and learning approaches on scientific attitudes in science of private MTs students in South Tangerang City. The implications of this research are: (1). It is hoped that educators in teaching and learning activities can choose the right learning approach to stimulate student enthusiasm and learning activities, such as an interactive approach that can create an active learning atmosphere. (2). Learning methods or learning styles are not inherited from within students, but are largely determined by the environment designed by the teacher. Therefore, teachers need to pay attention to the learning styles of students. 3. There is a need for construct validation on the instrument to strengthen the findings of other research results.